ANALISIS PENGARUH KOMPENSASI TERHADAP MANAJEMEN LABA - April Dwi Wulandari; Nur Syndah Apriliani; Gideon Setyo Budiwitjaksono (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
Compensation is all income in the form of money, goods directly or indirectly received by employees in return for services provided to the company. The purpose of this study was to examine the effect of compensation on earnings management. This research uses quantitative research through literature study by understanding and studying theories from various literatures related to the research. The data collection technique in this study uses a literature study by reviewing books, literature, scientific journals and previous research that has a relationship with the problems in the research. The results of this study indicate that compensation has no effect on earnings management.